Trade unions and the challenge of fostering solidarities in an era of financialisation. (August 2019) - Grady, Jo; Simms, Melanie
This articles re-examines evidence that trade unions in the UK have struggled to renew themselves despite considerable investment of time and effort. It argues that financialisation in the realms of capital accumulation, organisational decision making and everyday life has introduced new barriers to building the solidarities within and between groups of workers that would be necessary to develop a stronger response to the catastrophic effects on labour of financialisation in general, and the financial crisis specifically. The crisis highlighted the weaknesses of trade unions as institutions of economic and industrial democracy, but has also given some opportunities to establish narratives of solidarity in spaces and platforms created within a financialised context.